A method for growing multi-section temperature zone controlled calcium-magnesium-zirconium doped gadolinium gallium garnet crystal

CN122791472BActive Publication Date: 2026-10-27WUHAN TUOCAI TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611307785.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-27
Publication Date
2026-10-27
Estimated Expiration
2046-08-27

AI Technical Summary

Technical Problem

[0005]为解决现有技术中钙镁锆掺杂钆镓石榴石(SGGG)晶体生长时,固相法原料混合不均导致的组分偏析与第二相析出、传统热场无法解耦固液界面高温度梯度与已生长晶体低温度梯度所引发的热应力集中与位错增殖、分段加热结构热流突变造成的径向温差过大,以及异质籽晶引晶时晶格失配应力集中导致的晶体开裂和成品率低等技术问题,本发明提供了一种多段温区控制钙镁锆掺杂钆镓石榴石晶体的生长方法

Benefits of technology

[0016]相比于现有技术,本发明至少具有以下有益效果:采用溶胶-凝胶法制备多元氧化物纳米复合前驱体,使Gd、Ca、Ga、Mg和Zr在溶液尺度实现均匀混合,缩短烧结扩散距离,可有效减少组分偏析及Gd2Zr2O7第二相的形成,提高多晶原料的成分均匀性。通过设置熔体加热区、界面调控区、梯度过渡区和缓冷区,并对各温区进行独立及联动控制,实现固液界面较高轴向温度梯度与已生长晶体较低温度梯度的解耦,兼顾结晶驱动力和热应力释放,有利于稳定固液界面并抑制位错增殖和晶体开裂。采用连续复合辐射筒及相邻加热段重叠结构,可减小温区交界处的温度突变和径向温差,降低晶体内部热应力及生长条纹。采用与目标晶体组成匹配的〈111〉籽晶,并结合晶体直径、熔体弯月面高度和各温区温度的多变量反馈控制,可降低晶格失配应力,提高控径精度和生长稳定性。通过分段降温进一步缓释残余热应力,从而有利于获得大尺寸、成分均匀、低位错、低开裂且光学性能良好的钙镁锆掺杂钆镓石榴石晶体。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122791472B_ABST
    Figure CN122791472B_ABST
Patent Text Reader

Abstract

The application discloses a growth method of a multi-section temperature zone controlled calcium-magnesium-zirconium doped gadolinium gallium garnet crystal, and belongs to the technical field of crystal materials. The method comprises the following steps: preparing a nano composite precursor by a sol-gel method and sintering the nano composite precursor into a polycrystal block; melting the polycrystal block in a growth furnace which is provided with a melt heating zone, an interface regulation zone, a gradient transition zone and a slow cooling zone; adopting a same composition seed crystal to adopt a pulling growth method, and linking and adjusting the power of each temperature zone, so as to accurately control the axial temperature gradient of the solid-liquid interface and the slow cooling zone and the radial temperature difference; and finally, segmentally cooling. The application effectively solves the problems of multi-component segregation and thermal stress concentration, inhibits dislocation proliferation and crystal cracking, and can prepare a large-size, high-uniformity, low-defect and high-quality crystal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of crystal material technology, specifically, it relates to a method for controlling the growth of calcium magnesium zirconium doped gadolinium gallium garnet crystals in multiple temperature zones. Background Technology

[0002] Gadolinium gallium garnet (GGG) crystals are widely used in optoelectronic devices such as solid-state lasers and optical isolators due to their excellent magneto-optical, laser, and thermal properties. To perfectly match its lattice constant with specific magnetic thin films (such as bismuth-substituted rare-earth iron garnet films), it is usually necessary to introduce elements such as calcium (Ca), magnesium (Mg), and zirconium (Zr) into the GGG lattice for co-doping, forming calcium-magnesium-zirconium-doped gadolinium gallium garnet (SGGG) crystals. As epitaxial substrates for high-quality magneto-optical thin films, SGGG crystals place extremely high demands on their lattice uniformity, optical transmittance, and defect density such as dislocations.

[0003] Currently, SGGG crystals are mainly grown using the Czochralski method, with polycrystalline raw materials typically prepared via solid-state methods (i.e., mechanical mixing of high-purity oxide powder followed by high-temperature sintering). However, in actual production, existing technologies suffer from the following significant drawbacks: First, the radii and valences of various dopant ions such as Ca, Mg, and Zr differ considerably, making it difficult to achieve uniform dispersion at the atomic or nanoscale using traditional solid-state mechanical mixing. This leads to easy compositional segregation and the formation of second phases such as Gd₂Zr₂O₇ in the sintered material, causing localized supercooling upon entering the melt, resulting in inclusions, spiral growth, and severe fluctuations in the axial lattice constant of the grown crystals. Second, the growth of large-size, multi-component garnet crystals places extremely stringent requirements on the thermal field. The solid-liquid interface requires a high axial temperature gradient to provide the crystallization driving force and maintain a planar interface, while the grown crystal requires a lower temperature gradient to slowly release thermal stress. Traditional Czochralski furnaces typically employ a single melt heating zone and a simple post-heating insulation structure, failing to effectively decouple the "high interface gradient" from the "low crystal gradient." A low interface gradient can easily lead to component overcooling and uncontrolled diameter growth; while a high overall gradient can cause thermal stress concentration within the crystal, leading to massive dislocation multiplication and even through-cracks. Furthermore, traditional growth furnaces often have independently segmented insulation cylinders and heating elements, lacking heat flow transitions at the boundaries of adjacent temperature zones, resulting in significant temperature inflection points and abrupt heat flow changes. This leads to excessive radial temperature differences across the same cross-section of the crystal, further exacerbating thermal stress concentration and the formation of growth streaks. Finally, some existing technologies use pure GGG seed crystals to guide the growth of SGGG crystals. However, the doping of Ca, Zr, and other ions significantly increases the lattice constant of the target crystal, resulting in a significant lattice mismatch between the pure GGG seed crystal and the melt. This mismatch stress is easily concentrated and released during the seeding and shoulder formation stages, leading to seed crystal fracture or shoulder cracking, severely reducing the yield of large-size crystals.

[0004] Therefore, there is an urgent need in this field to develop a method for growing calcium magnesium zirconium-doped gadolinium gallium garnet crystals that can effectively improve the uniformity of multi-component raw materials, accurately decouple and control the temperature gradient of multiple temperature zones, and reduce thermal stress and lattice mismatch stress, so as to obtain high-quality crystals with large size, high uniformity and low defects. Summary of the Invention

[0005] To address the technical challenges in the growth of calcium magnesium zirconium-doped gadolinium gallium garnet (SGGG) crystals in existing technologies, such as component segregation and second-phase precipitation due to uneven mixing of raw materials in the solid-state method, thermal stress concentration and dislocation multiplication caused by the inability of traditional thermal fields to decouple the high temperature gradient at the solid-liquid interface from the low temperature gradient of the grown crystal, excessive radial temperature difference caused by abrupt changes in heat flow in the segmented heating structure, and crystal cracking and low yield due to lattice mismatch stress concentration during heterogeneous seed crystal introduction, this invention provides a multi-segment temperature zone controlled growth method for calcium magnesium zirconium-doped gadolinium gallium garnet crystals. This invention aims to achieve atomic-level homogeneous blending using nanoscale multi-component oxide precursors, decouple the interfacial crystallization driving force and crystal thermal stress release using multiple independent temperature zones and a continuous composite radiation cylinder, and combine seed crystal matching with the same composition and multivariate linkage feedback to effectively suppress component segregation, reduce thermal stress and lattice mismatch stress, ultimately producing large-size, high-axial-uniformity, low-dislocation-density, and crack-free high-quality SGGG single crystals.

[0006] The present invention adopts the following technical solution: a method for growing calcium magnesium zirconium doped gadolinium gallium garnet crystals by controlling the temperature of the crystals in multiple temperature zones, comprising the following steps: (1) growing the crystals according to the chemical formula Gd 3-x Ca x Ga 5-x-2y Mg y Zr x+y O 12A mixed salt solution containing gadolinium, calcium, gallium, magnesium and zirconium was prepared according to the corresponding cation ratio, wherein 0.31≤x≤0.40, 0.15≤y≤0.32, and 0.52≤x+y≤0.65; the mixed salt solution was subjected to complexation, gelation, drying and calcination in sequence to obtain a multi-component oxide nanocomposite precursor with a primary particle median size of 50-300nm; the nanocomposite precursor was shaped and sintered into a polycrystalline block, wherein Ga2O3 was in excess by 1.5-3.0wt% relative to the stoichiometry corresponding to the chemical formula; (2) the polycrystalline block was placed in an iridium crucible and placed in a melt heating zone, an interface control zone, a gradient transition zone and a slow cooling zone arranged in sequence along the pulling direction; the interface control zone, gradient transition zone and slow cooling zone were respectively provided with independent heating elements and temperature sensors; the polycrystalline block was heated to 1730-1800 (3) Using calcium magnesium zirconium doped gadolinium gallium garnet seed crystals with a growth direction of <111>, crystal initiation, necking, shoulder formation, equal diameter growth and tailing are carried out in sequence; during the crystal growth process, the temperature of each temperature zone, crystal diameter and melt meniscus height are collected, and the heating power of the interface control zone, gradient transition zone and slow cooling zone is adjusted in linkage through a multivariable controller so that the axial temperature gradient at the solid-liquid interface is maintained at 3.5-7.0℃ / cm, the axial temperature gradient of the part of the crystal located in the slow cooling zone is maintained at 0.5-2.5℃ / cm, and the maximum radial temperature difference between the axis and the outer periphery on the same axial section of the crystal is not greater than 2.0℃; (4) after the tailing is completed, the crystal is cooled in segments by passing through the gradient transition zone and slow cooling zone in sequence, and the maximum radial temperature difference is maintained below 2.0℃ during the cooling process until the crystal temperature drops below 500℃.

[0007] Preferably, in the chemical formula, 0.31≤x≤0.36, 0.25≤y≤0.32, 0.59≤x+y≤0.65, and the molar ratio of Ca to Mg is 0.95-1.15; the room temperature lattice constant of the obtained crystal is 12.450-12.510 Å.

[0008] Preferably, in step (1), Gd2O3 and Ga2O3 are dissolved in nitric acid solution, and calcium nitrate, magnesium nitrate and zirconium oxynitrate are added to form a mixed salt solution with a total metal ion concentration of 0.2-1.0 mol / L; citric acid is added as a complexing agent, the molar ratio of citric acid to total metal ions is 1.0-2.0, the pH of the solution is adjusted to 6.5-8.0, a gel is formed at 80-120℃, and calcined at 800-1050℃ for 2-6 hours.

[0009] Preferably, the median particle size of the primary particles in the nanocomposite precursor is 50-150 nm, and the particle size D90 is not greater than 300 nm. The particle size of the primary particles is obtained by statistical analysis of no less than 200 particles using transmission electron microscopy. The sum of the mass fractions of the garnet phase and the Ga2O3 compensating phase, as determined by Rietveld X-ray diffraction after sintering of the polycrystalline block, is not less than 99.0%, and the mass fraction of the Gd2Zr2O7 phase is not higher than 0.5%. In any five 100 μm × 100 μm scanning electron microscope energy spectrum scanning regions, the relative standard deviations of the atomic fractions of Ca, Mg, and Zr are not greater than 5%.

[0010] Preferably, the polycrystalline material is a columnar or sheet-like material with a diameter of 10-30 mm and a relative density of 55%-75%; an annular iridium cap is provided above the iridium crucible, and the central opening area of ​​the annular iridium cap is 20%-40% of the area of ​​the mouth of the iridium crucible; the molten material and crystal growth are carried out in nitrogen or argon gas with a purity of not less than 99.999%, and the absolute pressure inside the furnace is 0.10-0.15 MPa.

[0011] Preferably, an integral, continuous zirconia-alumina composite radiant tube that runs through the three temperature zones is provided inside the interface control zone, gradient transition zone, and slow cooling zone; the effective heating sections of the heating elements in two adjacent temperature zones overlap each other by 5-20 mm in the axial direction; the axial heights of the interface control zone, gradient transition zone, and slow cooling zone are 40-80 mm, 60-120 mm, and 80-160 mm, respectively.

[0012] Preferably, the axial temperature gradients at the solid-liquid interface during the necking stage, shoulder formation stage, constant diameter growth stage, and tailing stage are controlled to be 5.0-7.0℃ / cm, 4.0-6.0℃ / cm, 3.5-5.0℃ / cm, and 3.0-4.5℃ / cm, respectively; the axial temperature gradient is the slope of the linear fitting of the temperature-axial position curve within a 10mm axial interval centered on the solid-liquid interface; the height of the melt meniscus during the constant diameter growth stage is maintained at 0.8-2.5mm.

[0013] Preferably, the seed crystal is a <111> oriented seed crystal obtained by cutting and oriented processing a constant-diameter segment from a calcium magnesium zirconium doped gadolinium gallium garnet mother crystal with the same nominal composition as the target crystal; the mother crystal can be obtained by pulling growth from a garnet single crystal transition seed crystal with similar composition; the room temperature lattice mismatch rate between the seed crystal and the target crystal is not greater than 0.02%; the pulling speed during the constant-diameter growth stage is 0.8-1.5 mm / h, the seed crystal rotation speed is 4-8 rpm, the target crystal diameter is 50-80 mm, and the deviation of the crystal diameter from the target diameter is kept within ±0.5 mm.

[0014] Preferably, after the end of the process, the crystal is kept rotating at 1-3 rpm and cooled in stages according to the following cooling procedure: when the temperature drops from the crystal growth termination temperature to 1400℃, the cooling rate is 5-15℃ / h; when the temperature drops from 1400℃ to 900℃, the cooling rate is 10-25℃ / h; when the temperature drops from 900℃ to 500℃, the cooling rate is 20-40℃ / h; and after the temperature drops below 500℃, the furnace is cooled to room temperature.

[0015] Preferably, the diameter of the constant-diameter segment of the obtained crystal is not less than 50 mm and the effective length is not less than 80 mm; the difference in lattice constant at different axial positions of the constant-diameter segment is not greater than 0.002 Å; the full width at half maximum (FWHM) of the X-ray rocking curve of the (888) crystal plane is not greater than 2.0′; and the dislocation density of the (111) crystal plane measured by phosphoric acid etching is not greater than 100 cm⁻¹. -2 The transmittance of a double-sided polished wafer with a thickness of 2mm is not less than 80% in the 380-3000nm wavelength band.

[0016] Compared to existing technologies, this invention has at least the following advantages: The sol-gel method is used to prepare multi-component oxide nanocomposite precursors, enabling uniform mixing of Gd, Ca, Ga, Mg, and Zr at the solution scale, shortening the sintering diffusion distance, effectively reducing component segregation and the formation of the Gd₂Zr₂O₇ second phase, and improving the compositional uniformity of the polycrystalline raw material. By setting up a melt heating zone, interface control zone, gradient transition zone, and slow cooling zone, and independently and in conjunction with each temperature zone, the high axial temperature gradient at the solid-liquid interface and the lower temperature gradient of the grown crystal are decoupled, balancing crystallization driving force and thermal stress release, which is beneficial for stabilizing the solid-liquid interface and inhibiting dislocation proliferation and crystal cracking. The use of a continuous composite radiation cylinder and an overlapping structure of adjacent heating sections can reduce temperature abrupt changes and radial temperature differences at the temperature zone boundaries, reducing internal thermal stress and growth streaks within the crystal. Using a <111> seed crystal matched to the target crystal composition, combined with multivariable feedback control of crystal diameter, melt meniscus height, and temperature of each temperature zone, can reduce lattice mismatch stress and improve diameter control accuracy and growth stability. Segmented cooling further mitigates residual thermal stress, which is beneficial for obtaining large-sized, uniformly composed, low-dislocation, low-cracking calcium-magnesium-zirconium-doped gadolinium-gallium garnet crystals with good optical properties. Attached Figure Description

[0017] Figure 1 This is a phase composition diagram of the calcium magnesium gallium zirconium garnet crystal in Example 1.

[0018] Figure 2 This is a SEM-EDS elemental distribution map of five regions of the calcium magnesium gallium zircon garnet crystal in Example 1.

[0019] Figure 3This is a cross-sectional view of the multi-segment temperature-controlled calcium-magnesium-zirconium-doped gadolinium-gallium garnet crystal growth furnace (modified based on the JGD-60 model) in Example 1.

[0020] In the diagram: 1-Crystal, 2-Continuous composite radiation cylinder, 3-Three-section auxiliary heating element, 4-Insulation material, 5-Heat insulation material, 6-Furnace shell. Detailed Implementation

[0021] The present invention will be further described below with reference to specific embodiments. The listed embodiments are used to illustrate the technical concept and possible implementation methods of the present invention and are not intended to limit the scope of protection of the present invention. Unless otherwise stated, all percentages are mass percentages, the water is deionized water with a resistivity of not less than 18.2 MΩ·cm, the purity of all gases is not less than 99.999%, and the room temperature is 23±2℃. Unless otherwise specified, the present invention assumes that high-temperature related reactions are carried out under an inert atmosphere; simultaneously, the iridium crucible employs high-frequency induction heating.

[0022] The "same-composition SGGG seed crystal" referred to in this invention refers to a calcium-magnesium-zirconium-doped gadolinium-gallium garnet single crystal seed crystal with the same nominal chemical composition as the target crystal to be grown, and a room-temperature lattice mismatch rate of no more than 0.02%. The same-composition SGGG seed crystal does not necessarily have to be obtained simultaneously in this production process. It can be prepared from a same-composition SGGG parent crystal obtained from a previous growth process, or it can be obtained from a commercially available or prepared garnet single crystal with a similar composition as a transition seed crystal, after one or more transition pulling processes. The preparation of the first batch of SGGG seed crystals with the same composition includes: selecting a compositionally similar garnet single crystal with a <111> orientation as a transition seed crystal; using the same melt composition as the target crystal for seeding, necking, shoulder formation, and small-diameter constant-diameter growth; cutting <111> oriented wafers or rods from the compositionally stable constant-diameter section in the middle of the obtained transition crystal; determining the lattice constant of these wafers using X-ray diffraction and ICP-OES composition analysis; and selecting portions with a room-temperature lattice mismatch rate of no more than 0.02% and free of visible cracks and inclusions to process into SGGG seed crystals with the same composition for formal growth. When a compositionally similar garnet transition seed crystal is unavailable, a small-sized transition crystal can be prepared using a pure GGG seed crystal; however, due to the large lattice mismatch between pure GGG and the target SGGG, this route is only used to obtain subsequent SGGG seed crystals with the same composition and is not used as a conventional seeding method for large-sized target crystals in mass production. SGGG seed crystals with the same composition cut from the transition crystal are used for subsequent formal growth to reduce lattice mismatch stress in the seeding and shoulder regions. For example, CN101307496B discloses a technical route for directional growth of garnet melt using GYSGG single crystals or YSGG single crystals as seed crystals.

[0023] In this invention, zirconium oxynitrate exists in the form of zirconyl ions, which are prone to hydrolysis and hydroxy-bridged polymerization under near-neutral conditions without sufficient complexation. Therefore, zirconium oxynitrate does not come into direct contact with ammonia. Specifically, the zirconium-containing mixed salt solution is first maintained under acidic conditions, then citric acid is added and stirred to ensure that the molar ratio of citric acid to zirconium ions is not less than 6.0. After complexation is complete, ammonia is added dropwise to adjust the pH. The pH adjustment process controls the system temperature to not exceed 40°C and avoids localized, instantaneous high pH.

[0024] After adjusting to the target pH, the complexed solution should remain clear and transparent after standing at 25±2℃ for 2 hours, without any visible flocculent matter, sediment, or persistent turbidity. When the solution is filtered through a 0.45μm polytetrafluoroethylene (PTFE) membrane, no visible inorganic deposits should appear on the membrane. Complexed solutions that meet the above conditions should proceed to the subsequent gelation step; solutions that do not meet these conditions should not be used to prepare precursors.

[0025] In this application, "gadolinium nitrate aqueous solution," "gallium nitrate aqueous solution," "calcium nitrate aqueous solution," and "magnesium nitrate aqueous solution" all refer to solutions of the corresponding nitrates formed with water as a solvent. To make the form of the raw materials and the type of solvent clearer, the term "aqueous solution" is retained.

[0026] In this invention, the nominal composition of calcium magnesium zirconium doped gadolinium gallium garnet is Gd 3-x Ca x Ga 5-x-2y Mg y Zr x+y O 12 The term "oxide equivalent" refers to the mass of oxide obtained by igniting a sample of the corresponding nitrate solution at 1000℃ to constant weight; "Ga2O3 excess 2.0%" means that the actual amount of Ga2O3 added is equal to 1.020 times the theoretical stoichiometric amount of Ga2O3. Each nanocomposite precursor was prepared based on a theoretical stoichiometric amount of 500.0 g of oxides, and six portions were combined as the initial crystal growth feed.

[0027] The main raw materials and reagents used in this embodiment are shown in Table 1. The oxide equivalent of each metal nitrate stock solution was determined by mass method, and the metal content was verified by inductively coupled plasma atomic emission spectrometry. The stock solutions were filtered through a 0.45 μm polytetrafluoroethylene filter membrane before use.

[0028] Table 1 Main raw materials and reagents

[0029]

[0030] The main equipment includes: a 10L jacketed glass reactor (Shanghai Shensheng GR-10L type), a top-mounted stirrer (IKAEUROSTAR 100 digital type), a precision pH meter (Mettler-Toledo SevenCompact S220 type), a forced-air drying oven (Shanghai Yiheng DHG-9240A type), a high-temperature box furnace (Nabertherm HT 16 / 18 type), an air jet mill (Yixing Jingxin MQW03 type), a hydraulic tablet press (Tianjin Keqi YP-40T type), a cold isostatic press (Sichuan Aviation LDJ200 / 600-300 type), an automatic diameter control crystal growth furnace (JGD-60 modified type), a dual-color infrared thermometer (LumaSense IMPAC ISR 12-LO type), an industrial camera (Basler ace acA1920-155um type), and an NI cDAQ-9178 data acquisition and control system.

[0031] The aforementioned multi-segment thermal field can be achieved by modifying the thermal field components on a commercial Czochralski single crystal growth furnace platform. This embodiment uses a JGD-60 automatic diameter-controlled crystal growth furnace as the basic furnace body, adding a three-segment auxiliary heating element 3, a continuous composite radiation cylinder 2, and corresponding temperature detection and power control circuits above its original melt heating zone. The JGD series Czochralski single crystal furnace can serve as an automatic control single crystal furnace platform for oxide crystal pulling growth; in actual implementation, a similar commercial Czochralski crystal growth furnace with independent temperature zone power output, seed crystal pulling / rotation, inert atmosphere control, and temperature and crystal diameter acquisition interfaces can also be used for equivalent modification. It should be noted that the commercial basic furnace model is only used to illustrate that the thermal field structure of this application has a feasible equipment carrier. The three-segment auxiliary temperature zone formed by the three-segment auxiliary heating element 3, the continuous composite radiation cylinder 2, and the axially overlapping structure of the heating sections described in this application are thermal field components designed for SGGG crystal growth requirements, and do not imply that the commercial basic furnace has the above structure in its factory state.

[0032] The crystal growth furnace adds an interface control zone, a gradient transition zone, and a slow cooling zone above the original melt heating zone. For example... Figure 3As shown, crystal 1 is located in the lifting channel at the center of the furnace body; the three temperature zones correspond to the three independent annular graphite resistance heating sections of the three-section auxiliary heating body 3, and an integral continuous zirconia-alumina continuous composite radiation cylinder 2 is set on the inner side of the three-section auxiliary heating body 3; the continuous composite radiation cylinder 2 has an inner diameter of 125mm, an outer diameter of 141mm, and a total height of 300mm, wherein the mass ratio of yttrium-stabilized zirconia to alumina is 70:30. Thermal insulation material 4 and heat insulation material 5 are set around the outer periphery of the three-section auxiliary heating body 3, and the outermost layer of the furnace body is the furnace shell 6. The effective heights of the interface control zone, gradient transition zone, and slow cooling zone are 60mm, 90mm, and 120mm, respectively, and the effective heating sections of two adjacent heating sections of the three-section auxiliary heating body 3 overlap by 10mm in the axial direction. The melt heating zone is monitored using a type B platinum-rhodium thermocouple and a dual-color infrared thermometer, while the gradient transition zone and slow cooling zone are monitored using a type S platinum-rhodium thermocouple.

[0033] To further clarify the specific spatial arrangement of the three temperature zones and the overlap of adjacent heating sections, the interface control zone, gradient transition zone, and slow cooling zone are coaxially arranged from bottom to top along the lifting direction of crystal 1, and are all located on the outer periphery of the crystal 1 lifting channel above the iridium crucible. The interface control zone is mainly located near the predetermined solid-liquid interface, with an effective height of 60 mm; the gradient transition zone is immediately above it with an effective height of 90 mm; and the slow cooling zone is immediately above the gradient transition zone with an effective height of 120 mm. The three heating sections of the three-section auxiliary heater 3 correspond to the interface control zone, gradient transition zone, and slow cooling zone, respectively, and can be independently adjusted; each heating section is a ring-shaped graphite resistance heater, arranged around the lifting axis of crystal 1. "The effective heating sections of two adjacent temperature zones overlap by 10mm in the axial direction" means that the upper effective heating section of the first interface control zone heating section of the three-section auxiliary heating body 3 and the lower effective heating section of the second gradient transition zone heating section have a common coverage height of 10mm along the lifting axis. The upper effective heating section of the second gradient transition zone heating section and the lower effective heating section of the third slow cooling zone heating section also have a common coverage height of 10mm. This overlap does not mean that the two heating sections are in radial contact or mechanically stacked, but rather that their effective radiation heating range overlaps in the axial position. The three-section auxiliary heating element 3 has an inner diameter of 125 mm, an outer diameter of 141 mm, and a total height of 300 mm inside, forming an integral continuous zirconia-alumina composite radiation cylinder 2. The continuous composite radiation cylinder 2 is coaxial with the lifting axis of the crystal 1 and continuously spans the interface control zone, gradient transition zone, and slow cooling zone in the axial direction. This allows the radiant heat generated by the three-section auxiliary heating element 3 to first act on the continuous composite radiation cylinder 2, and then the continuous composite radiation cylinder 2 to perform secondary radiative heat exchange to the crystal 1 and its surrounding space. Thus, while retaining the independent adjustment capability of the three temperature zones, the continuous radiation surface and the axially overlapping heating sections weaken the abrupt changes in heat flow at the boundaries of adjacent temperature zones. The three-section auxiliary heating element 3, arranged from bottom to top along the pulling direction (+Z) of the crystal 1, consists of: the first section, the interface control zone heating section, with an effective height of 60 mm, whose upper end overlaps with the second section by 10 mm; the second section, the gradient transition zone heating section, with an effective height of 90 mm, whose upper and lower ends each overlap with the adjacent section by 10 mm; and the third section, the slow cooling zone heating section, with an effective height of 120 mm, whose lower end overlaps with the second section by 10 mm. Adjacent heating sections of the three-section auxiliary heating element 3 overlap 10 mm axially. This overlap is axial and not radial contact or mechanical stacking.

[0034] This Example 1 is a preferred embodiment, fully encompassing the preparation of a multi-component oxide nanocomposite precursor, preparation of polycrystalline blocks, multi-segment thermal field calibration, seed crystal pulling growth with the same composition, and segmented slow cooling. The nominal composition of the target crystal is Gd. 2.66 Ca 0.34 Ga 4.06 Mg0.30 Zr 0.64 O 12 .

[0035] Preparation of the nanocomposite precursor: Each precursor is based on a theoretical stoichiometric total oxide amount of 500.0 g. The theoretical Ga2O3 equivalent is 195.6 g, and after a 2.0% volatilization compensation, the actual Ga2O3 equivalent is 199.5 g. The specific amounts of each raw material are shown in Table 2.

[0036] Table 2. Amount of metal salt per part of precursor in Example 1

[0037]

[0038] Table 3 Auxiliary raw materials and control parameters for each precursor in Example 1

[0039]

[0040] Preparation of mixed salt solution: 1239.2 g of gadolinium nitrate aqueous solution, 49.0 g of calcium nitrate aqueous solution, and 31.1 g of magnesium nitrate aqueous solution were sequentially added to a 10 L jacketed glass reactor and stirred at 25 °C and 500 rpm for 20 min. 202.7 g of zirconium oxynitrate aqueous solution was added at a rate of 20.0 g / min, and stirring continued for 30 min. Then, 997.6 g of gallium nitrate aqueous solution was added, and stirring continued for 40 min to obtain a clear mixed salt solution. Complexation and pH adjustment: 917.8 g of anhydrous citric acid was added to 1200.0 g of deionized water and stirred at 45 °C and 400 rpm until completely dissolved. The mixed salt solution was added at a rate of 30.0 g / min, maintaining the reaction temperature below 35 °C and stirring at 600 rpm. After the addition was complete, stirring continued for 60 min, and then 25.0 wt% ammonia water was added dropwise at a rate of 5.0 g / min, for a total addition of 468.0 g, to achieve a pH of 7.20. After the pH stabilized for 10 minutes with a change not exceeding 0.03, it was aged at 35℃ for 60 minutes. Gelation and drying: The jacket temperature was raised to 85℃, and the mixture was concentrated by stirring at 300 rpm for 4.0 hours until the apparent viscosity at 25℃ reached 92 mPa·s. The concentrated sol was then dispensed into PTFE-lined stainless steel trays with a layer thickness controlled at 12 mm, and dried at 120℃ for 12 hours to obtain a loose dry gel. Fractional calcination: The dry gel was broken into pieces smaller than 10 mm, heated to 350℃ at 1℃ / min and held for 2 hours, then heated to 650℃ at 2℃ / min and held for 2 hours, then heated to 1000℃ at 3℃ / min and held for 6 hours, followed by cooling to 300℃ at 3℃ / min with the furnace. Calcination was carried out in an air atmosphere. The obtained powder was subjected to air jet milling at a classifying wheel speed of 9000 rpm to obtain a nanocomposite precursor with a median particle size of approximately 108 nm and a particle size D90 of approximately 185 nm. The above operation was repeated six times. The total theoretical stoichiometric amount of oxides in the six precursors was 3000.0 g, the total Ga2O3 compensation amount was 23.5 g, and the target feed oxide equivalent of the combined powder after calcination was 3023.5 g. Polycrystalline block preparation: Molding: The combined powder was sieved through a 200-mesh sieve. Each time, 25.0 g of powder was weighed and placed into a 25 mm diameter cemented carbide mold, pre-pressed at 50 MPa for 30 s, and then held at 180 MPa for 60 s; the pre-pressed blank was placed in a vacuum rubber sleeve and cold isostatically pressed at 220 MPa for 5 min. Sintering: The pressed blank was placed in a covered high-purity alumina crucible, and sacrificial powder of the same composition was laid around the pressed blank. The temperature was increased to 600℃ at a rate of 2℃ / min and held for 2 hours, then increased to 1350℃ at a rate of 3℃ / min and held for 8 hours. The temperature was then decreased to 500℃ at a rate of 3℃ / min and cooled in the furnace. The resulting polycrystalline material block had a diameter of approximately 21.5 mm and a height of approximately 17.0 mm. The relative density, measured using a geometric method, was 66.3%. Acceptance: If... Figure 1As shown, X-ray diffraction (Rietveld) refinement confirmed that the sum of the mass fractions of the garnet phase and the Ga2O3 compensating phase was not less than 99.0%, and the Gd2Zr2O7 phase was not more than 0.5%; Figure 2 As shown, within the five 100μm×100μm scanning electron microscope energy dispersive spectroscopy (EDS) scanning regions, the relative standard deviations of the atomic fractions of Ca, Mg, and Zr are no higher than 5%. Materials that do not meet these criteria are not used for crystal growth. Multi-segment thermal field calibration: Thermal field calibration is performed before formal loading. An empty crucible with the same shape as the actual iridium crucible is placed in the growth position. The furnace is evacuated to 8 Pa and then filled with nitrogen to 0.12 MPa. The melt heating zone is raised to 1780℃, and the interface control zone, gradient transition zone, and slow cooling zone are set to 1670℃, 1570℃, and 1470℃, respectively. Type B and Type S thermocouples, calibrated at three points (1700℃, 1600℃, and 1500℃), are used to measure the temperature every 2 mm along the axial direction, with repeated measurements at the central axis, a radius of 25 mm, and a radius of 45 mm. With the predetermined solid-liquid interface height as the center, the temperature-position data were linearly fitted within a 10mm axial interval of 5mm above and below it, and the fitting slope was used as the axial temperature gradient of the solid-liquid interface; the maximum temperature difference between the crystal cross-section center and the outer periphery measurement point was used as the radial temperature difference. By adjusting the power of the three auxiliary temperature zones and the power distribution of the overlapping area of ​​adjacent heating sections, the axial temperature gradients of the interface corresponding to the necking, shouldering, constant diameter, and tailing stages reached 6.2℃ / cm, 5.0℃ / cm, 4.2℃ / cm, and 3.6℃ / cm, respectively; the axial temperature gradient of the slow cooling zone was 1.4℃ / cm; and the maximum radial temperature difference of the same axial cross-section was 1.2℃. The thermal field calibration curve was stored in the control system, and coordinate correction was performed according to the melt surface position during formal growth. Single crystal growth: charging and atmosphere replacement: 3023.5g of polycrystalline material was layered and loaded into an iridium crucible, and an annular iridium cap with a central opening diameter of 32mm was set on top of the crucible. The furnace body was evacuated to 8 Pa and then filled with nitrogen to 0.12 MPa. This evacuation-filling process was repeated three times to maintain an absolute pressure of 0.12 MPa inside the furnace, with nitrogen replenished at a rate of 0.5 L / min. Melting and homogenization: The temperature was increased to 1200℃ at 120℃ / h, then to 1700℃ at 60℃ / h, and finally to 1780℃ at 20℃ / h. After confirming complete melting of the raw material, it was held at 1780℃ for 6 hours. During the holding period, a small power disturbance of ±0.5% of the rated power was performed every 30 minutes, and the melt surface recovery time was observed to confirm the stability of the melt's thermal state. Crystal development: A nominal composition of Gd was used. 2.66 Ca 0.34 Ga 4.06 Mg 0.30 Zr 0.64 O 12A <111> oriented SGGG seed crystal was used. The room temperature lattice constant of the seed crystal was 12.4995 Å, and the nominal lattice mismatch rate with the target crystal was 0.005%. After preheating the seed crystal at 10 mm above the molten surface for 30 min, it was lowered to the molten surface at a rate of 2 mm / min and stabilized for 15 min before being pulled up.

[0041] like Figure 3 As shown, the three temperature zones do not operate as isolated isothermal zones, but rather work collaboratively in a manner that involves "the interface control zone providing a higher driving force for interfacial crystallization, the gradient transition zone smoothly reducing axial heat flow, and the slow cooling zone releasing the thermal stress of the grown crystal 1 at a lower gradient." During formal growth, the multivariable controller uses the temperature of each temperature zone, the diameter of crystal 1, and the height of the melt meniscus as feedback quantities to adjust the power of the three heating sections of the three-section auxiliary heating body 3 in a coordinated manner: the interface control zone controls the axial temperature gradient of the solid-liquid interface in the necking, shouldering, constant diameter, and tailing stages to around 6.2℃ / cm, 5.0℃ / cm, 4.2℃ / cm, and 3.6℃ / cm, respectively; the gradient transition zone gradually transitions the higher gradient near the interface to the slow cooling zone; and the slow cooling zone controls the axial temperature gradient of the grown crystal 1 to around 1.4℃ / cm. The continuous composite radiation cylinder 2 provides a continuous radiative heat transfer surface between the three temperature zones. The 10mm axial overlap between adjacent heating sections of the three-section auxiliary heater 3 compensates for insufficient direct heating power coverage near the temperature zone boundaries. Together, they transform the heat dissipation input formed by independent zone power adjustment into a smoother axial heat flow distribution, and control the maximum radial temperature difference of the same axial section of the crystal 1 to about 1.2℃. Therefore, the gradient temperature design solves the problem of axial gradient decoupling between the solid-liquid interface crystallization driving force and the low thermal stress of the grown crystal 1. The overlapping heating sections of the continuous composite radiation cylinder 2 and the three-section auxiliary heater 3 solve the problems of axial heat flow continuity and radial temperature difference at the zone heating boundaries. The three cooperate with each other in the same thermal field, rather than being independent of each other.

[0042] Table 4 Crystal growth parameters of Example 1

[0043]

[0044] During the growth of crystal 1, the temperature of each temperature zone, the weighing sensor signal, the diameter of crystal 1, and the height of the meniscus of the melt are collected at a frequency of 1Hz. An industrial camera acquires images of the outline and meniscus of crystal 1. The control system uses a 10-second sliding average value as feedback input to adjust the power of the three heating sections of the three-section auxiliary heating element 3 corresponding to the interface control zone, gradient transition zone, and slow cooling zone. When the diameter deviation is greater than 0.3mm, the lifting speed is corrected in steps not exceeding 0.05mm / h, and the single correction amount of the power of the three-section auxiliary heating element 3 is limited to within 0.3% of the rated power. During the constant diameter stage, the axial temperature gradient in the slow cooling zone is maintained at 1.4℃ / cm, and the radial temperature difference is not higher than 1.2℃. Segmented slow cooling and crystal removal: After the finishing stage, crystal 1 is lifted 5mm away from the melt, rotated at 2.0rpm, and lifted until the main part of the constant diameter section of crystal 1 is located in the gradient transition zone and slow cooling zone. The crystal was then cooled according to the following procedure: from the growth termination temperature to 1400℃ at a cooling rate of 10℃ / h; from 1400℃ to 900℃ at a cooling rate of 20℃ / h; from 900℃ to 500℃ at a cooling rate of 30℃ / h; once below 500℃, active heating was stopped and the crystal was cooled to room temperature in the furnace. During the cooling process, the three heating sections of the three-stage auxiliary heating element 3 were linked and controlled to ensure that the maximum radial temperature difference of the same cross section of crystal 1 did not exceed 2.0℃. After cooling to room temperature, crystal 1 was removed, and the seed crystal, shoulder, and tail were cut off to obtain a crystal with a constant diameter of approximately 52mm and an effective length of approximately 96mm. The wafer was cut along the growth direction perpendicular to <111> and used for lattice constant, rocking curve, dislocation, stress birefringence, transmittance, color, and microhardness testing.

[0045] Examples 2-4 are identical to Example 1 in basic process, equipment, measurement methods, and control logic. The only differences are in the components, precursor parameters, thermal field parameters, and growth parameters listed in Tables 5-7. Parameters not listed are the same as in Example 1.

[0046] Table 5. Compositions and precursor parameters that differ between Examples 2-4 and Example 1

[0047]

[0048] Table 6 Actual weighing differences of each precursor in Examples 2-4

[0049]

[0050] Table 7 Differences in thermal field and crystal growth in Examples 1-4

[0051]

[0052] Example 2 obtained a precursor with a smaller particle size at a lower x+y value and a lower calcination temperature, using a higher interface gradient and a faster pulling speed; Example 3 used a higher total substitution amount of Ca and Zr, and to reduce lattice distortion and composition fluctuation, the constant diameter pulling speed was reduced to 0.8 mm / h and the slow cooling zone gradient was increased to 2.2 °C / cm; Example 4 used a lower slow cooling zone gradient and a higher rotation speed to verify the applicability of the present invention under different heat flux distributions.

[0053] Each comparative example is based on Example 1. Except for the differences explicitly stated, the raw materials, equipment, steps and testing methods are the same as those in Example 1.

[0054] Comparative Example 1: Omitting the nanocomposite precursor process

[0055] According to the oxide equivalents of Example 1, 1487.0 g of high-purity gadolinium oxide, 58.8 g of calcium oxide, 1197.1 g of gallium oxide, 37.3 g of magnesium oxide, and 243.2 g of zirconium oxide were directly weighed, with gallium oxide already including a 2.0% compensation. The powder was placed in a V-type mixer and mixed at 25 rpm for 8 hours without solution complexation, gelation, or nano-sizing treatment; subsequently, polycrystalline blocks were prepared using the same pelletizing, isostatic pressing, and sintering process at 1350 °C as in Example 1. This comparative example was used to evaluate the effect of the homogeneity of multi-cation nanoscale blending on the second phase, component segregation, and dislocations.

[0056] Comparative Example 2: Eliminate the overlap of the heating sections of the continuous composite radiation cylinder 2 and the three-section auxiliary heating element 3.

[0057] The nanocomposite precursor and growth parameters of Example 1 were used, but the continuous composite radiation cylinder 2 was replaced with three separate alumina short cylinders, with a 10mm axial gap between adjacent short cylinders; the three heating sections of the three-section auxiliary heater 3 were not axially overlapped. The set temperatures of the controllers for each zone remained at 1670℃, 1570℃, and 1470℃, respectively. This comparative example was used to evaluate the abrupt changes in axial temperature and uneven radial heat flow caused by the segmented structure.

[0058] Comparative Example 3: The solid-liquid interface temperature gradient is too low

[0059] Using the precursor and thermal field structure of Example 1, the axial temperature gradient at the solid-liquid interface during the necking, shouldering, constant diameter, and tailing stages was set to 2.2℃ / cm; the axial gradient and radial temperature difference in the slow cooling zone remained at 1.4℃ / cm and 1.2℃, respectively. This comparative example was used to examine the risk of spiral growth and diameter runaway when the interfacial driving force was insufficient.

[0060] Comparative Example 4: Both the interface gradient and the slow cooling gradient are too high.

[0061] Using the raw materials and thermal field structure of Example 1, the axial gradients of the solid-liquid interface in the necking, shouldering, constant diameter, and tailing stages were set to 9.0℃ / cm, 8.5℃ / cm, 8.0℃ / cm, and 7.0℃ / cm, respectively. The axial gradient in the slow cooling zone was set to 4.0℃ / cm, and a radial temperature difference of 3.0℃ was allowed within the same cross-section. This comparative example was used to investigate thermal stress, dislocation propagation, and cracking caused by excessively high thermal gradients.

[0062] Comparative Example 5: Substitution Exceeds Limits

[0063] Adjust the target composition to Gd 2.60 Ca 0.40 Ga 3.90 Mg 0.35 Zr 0.75 O 12 Where x = 0.40, y = 0.35, and x + y = 0.75. The stock solutions of gadolinium nitrate, calcium nitrate, gallium nitrate, magnesium nitrate, and zirconium oxynitrate used in each 500.0g theoretical oxide batch were 1219.9g, 58.1g, 965.2g, 36.5g, and 239.2g, respectively; anhydrous citric acid 924.1g; and 25.0% ammonia 470.0g. The remaining steps were the same as in Example 1. This comparative example was used to investigate the effect of high zirconium substitution on Gd₂Zr₂O₇ precipitation and lattice distortion.

[0064] Comparative Example 6: Using pure GGG seed crystals

[0065] Using the raw materials, precursors, thermal field, and growth parameters of Example 1, only the SGGG seed crystal of the same composition was replaced with <111> oriented pure Gd3Ga5O. 12 Seed crystal. The pure GGG seed crystal used has a room temperature lattice constant of 12.383 Å and a nominal lattice mismatch rate of approximately 0.93% with the target SGGG crystal. This comparative example is used to evaluate the effect of the seed crystal lattice mismatch on the seeding region and shoulder cracks.

[0066] Comparative Example 7: Cancellation of Continuous Composite Radiation Cylinder 2

[0067] Using the nanocomposite precursor, set temperatures for each temperature zone, and crystal growth parameters from Example 1, only the structure of the radiant tubes inside the interface control zone, gradient transition zone, and slow cooling zone was changed. Specifically, the continuous composite radiant tube 2 in Example 1 was replaced with three separate alumina short tubes, with a 10mm axial gap between adjacent short tubes; the adjacent heating sections of the three-section auxiliary heating element 3 maintained the 10mm axial overlap from Example 1. The set temperatures of the three auxiliary temperature zone controllers remained 1670℃, 1570℃, and 1470℃, respectively, and the remaining raw material composition, charge quantity, atmosphere, interface axial temperature gradient, slow cooling zone axial temperature gradient, pulling speed, seed crystal rotation speed, and segmented cooling program were all the same as in Example 1. This comparative example was used to separately evaluate the effects of the continuous composite radiant tube 2 on the continuity of radiative heat flow at the temperature zone interface, radial temperature difference, crystal thermal stress, and growth striations.

[0068] Comparative Example 8: Eliminating the overlapping heating sections of the three-section auxiliary heating element 3

[0069] Using the nanocomposite precursor, set temperatures for each temperature zone, and crystal growth parameters from Example 1, the continuous composite radiation tube 2 was retained, but the 10mm axial overlap between adjacent heating sections of the three-section auxiliary heating element 3 was eliminated, ensuring that adjacent effective heating sections do not overlap axially. The set temperatures of the three auxiliary temperature zone controllers remained 1670℃, 1570℃, and 1470℃, respectively. All other aspects, including raw material composition, charge quantity, atmosphere, radiation tube structure, interface axial temperature gradient, slow cooling zone axial temperature gradient, pulling speed, seed crystal rotation speed, and segmented cooling program, were identical to those in Example 1. This comparative example was used to separately evaluate the impact of the overlapping structure of the heating sections of the three-section auxiliary heating element 3 on axial heat flow connection at the temperature zone interface, radial temperature difference, crystal thermal stress, and growth streaks.

[0070] Table 8 Comparative Design

[0071]

[0072] Test methods: Sol viscosity: The apparent viscosity of the concentrated sol was measured using a Brookfield DV2T rotational viscometer at 25.0℃ with rotor No. 2 and 60 rpm; each sample was measured in triplicate, and the average value was taken. Nanoparticle size: The calcined powder was observed using a JEOL JEM-2100F transmission electron microscope at 200 kV. At least 10 fields of view were randomly selected for each sample, and the equivalent circular diameters of at least 200 primary particles were counted to calculate D50 and D90. Phase and phase transformation: A Panalytical X'Pert PRO X-ray diffractometer was used with Cu Kα rays, tube voltage 40 kV, tube current 40 mA, 2θ range 20°-120°, and step size 0.02°. The mass fractions of garnet, Ga2O3, and Gd2Zr2O7 phases were calculated using the Rietveld method; the garnet phase transformation rate was expressed as the garnet phase mass fraction. Elemental homogeneity: A 100μm × 100μm area scan was performed on the sintered blocks at 15kV using a ZEISS GeminiSEM 500 scanning electron microscope and an Oxford X-Max 80 energy dispersive spectrometer. Five regions with a minimum spacing of 2mm were measured for each sample, and the relative standard deviations of the atomic fractions of Ca, Mg, and Zr were calculated. Relative density of polycrystalline blocks: The mass, diameter, and height of the blocks were measured, and the bulk density was calculated based on the geometric volume. The relative density was calculated using the X-ray theoretical density of the corresponding nominal composition as a reference. Ten blocks were randomly measured from each batch. Temperature field parameters: The furnace thermal field was calibrated using calibrated type B and type S thermocouples and a dual-color infrared thermometer. The axial temperature gradient was calculated using the slope of a linear fit over a 10mm interval centered on the solid-liquid interface; the radial temperature difference was the maximum temperature difference between the central axis and the outer perimeter measuring points at the same height. Crystal composition and axial segregation: Approximately 0.20 g samples were taken from the head, middle, and tail of the crystals and digested in a closed system using a nitric acid-hydrochloric acid mixture. The contents of Gd, Ca, Ga, Mg, and Zr were determined using an Agilent 5110 ICP-OES. The axial deviation of each element was calculated by dividing the difference between the maximum and minimum values ​​at the three locations by the average value. Crystal yield and appearance: The crystal yield was calculated as the ratio of the effective mass of the uniform-diameter crystals after removing obvious shoulder defects and the tail to the initial equivalent mass of oxide feed. Two mutually perpendicular diameters were measured every 10 mm along the uniform-diameter section using vernier calipers. Spirals, clouding, inclusions, cracks, and growth streaks were examined under transmitted white light and orthogonally polarized light. Lattice constant and axial uniformity: 2.0 mm thick (111) wafers were cut from the head, middle, and tail locations. The full spectrum was measured using a high-resolution X-ray diffractometer, and the lattice constant was refined. The axial lattice constant difference was the difference between the maximum and minimum values ​​at the three locations. Rocking curves: Rocking curves of the (888) crystal plane were determined using a Rigaku SmartLab high-resolution X-ray diffractometer with a step size of 0.001°. The results are expressed as full width at half maximum (FWHM). Three points were measured at each location, and the average value was taken.Dislocation density: The (111) wafer was polished on both sides until the surface roughness Ra≤1nm, etched in 85% phosphoric acid at 200℃ for 32min, cleaned and dried, and the corrosion pits were observed using a metallographic microscope. Ten pits with an area of ​​1.0mm were randomly selected. 2 Field counts and dislocation density were calculated by dividing the number of etch pits by the observed area. Stress birefringence: The optical path difference of a 10.0 mm thick sample was measured at 632.8 nm using a StrainScope S3 / 180 stress birefringence meter; the birefringence was calculated as Δn = optical path difference / sample thickness. Measurements were taken at the center and four locations 5 mm from the edge of each wafer, and the maximum value was recorded. Optical transmittance and color: The wafers were polished to 2.0 ± 0.02 mm on both sides, and transmittance was measured in the 380-3000 nm range using a PerkinElmer Lambda 1050+ spectrophotometer; the average transmittance without significant absorption was reported. CIE L*, a*, and b* values ​​were measured using a Konica Minolta CM-5 colorimeter in transmission mode, with b* representing the yellow tint. Microhardness: Using an HVS-1000A microhardness tester, a load of 4.903 N was applied to the (111) polished surface and held for 15 s. Ten points were measured for each wafer, and the average value was taken after removing the maximum and minimum values. Thermal cycling stability: Ten wafers with a diameter of 25 mm and a thickness of 2 mm were cycled 20 times between 25 °C and 200 °C. The heating and cooling rates were both 5 °C / min, and the wafers were held at each temperature for 20 min. Cracks were checked after cycling, and the change in transmittance was measured.

[0073] Table 9 Data on precursors and polycrystalline blocks

[0074]

[0075] Table 10 Data on crystal growth and properties

[0076]

[0077] Examples 1-4 employ a solution complexation-gelation route, enabling Gd, Ca, Ga, Mg, and Zr to be co-dispersed at the solution scale. After calcination, the primary particles are at the nanoscale, and the relative standard deviation of the Ca, Mg, and Zr surface scans can be controlled within 5%. In contrast, Comparative Example 1 directly mechanically mixes micron-sized oxide powders, increasing the short-range diffusion distance and easily forming zirconium-rich regions and the Gd₂Zr₂O₇ second phase in the sintered material. These non-uniform regions, upon entering the melt, cause localized undercooling, component segregation, and dislocation sources, resulting in helices, inclusions, and fluctuations in the axial lattice constant of the crystal. SGGG crystal growth simultaneously presents two opposing requirements: the solid-liquid interface needs to maintain sufficient crystallization driving force and a stable interface shape, while the grown crystal needs to slowly release heat in a low-gradient region. Examples 1-4 establish an interface gradient of 3.5-7.0℃ / cm through an interface control region, while simultaneously using a gradient transition region and a slow cooling region to reduce the axial gradient of the grown crystal to 0.5-2.5℃ / cm. Comparative Example 3 reduced the interface gradient to 2.2℃ / cm, resulting in insufficient driving force at the solid-liquid interface. This led to uneven undercooling near the three-phase line of the melt surface, manifesting as spirals and uncontrolled diameter. Comparative Example 4 simultaneously increased the interface and slow cooling gradients. Although the interface driving force was greater, the internal temperature difference and thermal stress of the crystal increased significantly, leading to dislocation multiplication and through-cracks. In Example 1, the continuous composite radiation tube 2 spanned three auxiliary temperature zones. The adjacent heating sections of the three-section auxiliary heater 3 overlapped axially by 10mm, converting the radiative heat flow of the discrete heater into a continuous axial heat flow and reducing the temperature inflection point at the section boundaries. In Comparative Example 2, after eliminating the 10mm axial overlap between adjacent heating sections of the continuous composite radiation tube 2 and the three-section auxiliary heater 3, even with unchanged center temperature settings in each zone, abrupt changes in heat flow and amplified radial temperature differences still occurred at the boundaries, making the crystal prone to shoulder cracks, growth streaks, and high-stress birefringence. 2+ Mg 2+ and Zr 4+ Co-substitution can adjust the lattice constant, but Zr 4+Larger radii and excessive substitution increase lattice distortion and promote Gd₂Zr₂O₇ precipitation. In Comparative Example 5, increasing x+y to 0.75 resulted in the expected appearance of a significant second phase, opacity, and a rapid increase in dislocation density. Comparative Example 6 used pure GGG seed crystals, and approximately 0.93% of the lattice mismatch between the seed crystal and the target SGGG was concentrated in the seeding and shoulder regions, thus easily leading to crack formation near the seed crystal and at the shoulder. Using a homologous <111> SGGG seed crystal significantly reduced this mismatch stress. Under the combined effects of the nanocomposite precursor, homologous seed crystals, continuous composite radiating tube 2, decoupling of high gradient and slow cooling low gradient at the interface, and multivariable feedback control, the goal of Examples 1-4 was to obtain transparent SGGG crystals with a diameter of not less than 50 mm and an effective length of not less than 80 mm, while achieving the defined or supported levels for axial lattice constant difference, full width at half maximum (FWHM) of the rocking curve, dislocation density, stress birefringence, and optical transmittance.

[0078] As shown in Table 10, in Comparative Example 7, after the continuous composite radiation tube 2 was removed but the three-section auxiliary heating body 3 was retained, the maximum radial temperature difference increased to 2.7℃ after the adjacent heating sections overlapped by 10mm. The effective diameter was 52.0±0.9mm, the effective length was 83mm, and the yield was 62.6%. Local shoulder cracks and growth streaks appeared in the crystal. The lattice constant was 12.5003Å, the axial lattice constant difference was 0.0037Å, the full width at half maximum (FWHM) of the X-ray rocking curve of the (888) crystal plane was 2.22′, and the dislocation density was 155cm. -2 Δn is 1.8 × 10 -6 The average transmittance was 79.1%, b* was 2.1, and HV0.5 was 724. Comparative Example 8 retained the continuous composite radiation tube 2 but removed the three-section auxiliary heating body 3. After the adjacent heating sections overlapped axially by 10 mm, the maximum radial temperature difference was 2.2℃, the effective diameter was 52.0±0.7 mm, the effective length was 88 mm, the yield was 67.4%, and the crystal showed growth stripes and slight shoulder marks; the lattice constant was 12.5002 Å, the axial lattice constant difference was 0.0028 Å, the full width at half maximum (FWHM) of the X-ray rocking curve of the (888) crystal plane was 2.05′, and the dislocation density was 110 cm⁻¹. -2 Δn is 1.3 × 10 -6The average transmittance was 80.2%, b* was 1.6, and HV0.5 was 729. The results show a general trend of deterioration from Example 1, Comparative Example 8, Comparative Example 7, to Comparative Example 2. Specifically, removing either the continuous composite radiation tube 2 or the 10mm axial overlap of adjacent heating sections of the three-section auxiliary heater 3 individually reduces the smoothness of heat flow at the temperature zone boundary and increases the radial temperature difference. The effect of removing the continuous composite radiation tube 2 is relatively more pronounced. When both structures are removed simultaneously, the abrupt change in heat flow and the radial temperature difference are further amplified. This trend indicates that the 10mm axial overlap of adjacent heating sections of the continuous composite radiation tube 2 and the three-section auxiliary heater 3 are both beneficial for reducing crystal thermal stress, suppressing dislocation multiplication and growth streaks, and their combined use has a better thermal field homogenization effect.

[0079] Furthermore, Comparative Examples 2, 7, and 8 were used to separately verify the effect of the aforementioned thermal field structure: Comparative Example 7 only eliminated the continuous composite radiation cylinder 2 while retaining the three-section auxiliary heating body 3 with adjacent heating sections overlapping axially by 10 mm. The maximum radial temperature difference increased from 1.2℃ in Example 1 to 2.7℃, and the dislocation density increased from 52 cm⁻¹. -2 Increased to 155cm -2 The average transmittance decreased from 82.8% to 79.1%; in Comparative Example 8, the continuous composite radiation tube 2 was retained while only the three-section auxiliary heating element 3 was removed, resulting in a 10mm axial overlap between adjacent heating sections, increasing the maximum radial temperature difference to 2.2℃ and the dislocation density to 110cm. -2 The average transmittance dropped to 80.2%; in Comparative Example 2, when the continuous composite radiation tube 2 and the three-section auxiliary heating body 3 were simultaneously removed and their adjacent heating sections overlapped by 10 mm axially, the maximum radial temperature difference further reached 3.4℃, and the dislocation density reached 220 cm⁻¹. -2 Shoulder cracks and growth streaks appear. This progressive trend indicates that the continuous composite radiation tube 2 can spatially homogenize the discrete radiative heat of three independent temperature zones. The axial overlap of the heating sections can compensate for the direct heating coverage at the boundary of adjacent temperature zones. Both play their respective roles and jointly reduce the heat flow abrupt change at the temperature zone boundary. On this basis, through the gradient division of labor in the interface control zone, gradient transition zone, and slow cooling zone, the higher axial gradient of the solid-liquid interface and the lower axial gradient of the grown crystal are maintained simultaneously. Therefore, the technical effect of this application does not simply come from the temperature value of a certain temperature zone or a certain structural component, but from the synergistic thermal field design of "multi-segment gradient division of labor + continuous radiative heat flow homogenization + overlapping heating compensation", which, together with the effect of the nanocomposite precursor in reducing component segregation, constitutes a synergistic control scheme for large-size multi-component SGGG crystals.

[0080] The above embodiments are for illustrative purposes only. Those skilled in the art can make adaptive adjustments to the metal salt source, equivalent equipment, temperature zone size, and control algorithm without departing from the concept of the invention; however, such adjustments should satisfy the limitations regarding composition, nanocomposite precursors, multi-segment temperature zone structure, interface temperature gradient, slow cooling temperature gradient, radial temperature difference, seed crystals of the same composition, and segmented cooling.

Claims

1. A method for growing calcium-magnesium-zirconium-doped gadolinium-gallium garnet crystals using multi-segment temperature control, characterized in that: Includes the following steps: (1) According to the chemical formula Gd 3-x Ca x Ga 5-x-2y Mg y Zr x+y O 12 A mixed salt solution containing gadolinium, calcium, gallium, magnesium, and zirconium was prepared according to the corresponding cation ratios, wherein 0.31≤x≤0.40, 0.15≤y≤0.32, and 0.52≤x+y≤0.65; the mixed salt solution was subjected to complexation, gelation, drying, and calcination in sequence to obtain a multi-component oxide nanocomposite precursor with a median primary particle size of 50-300 nm; the nanocomposite precursor was shaped and sintered into a polycrystalline block, wherein Ga2O3 was in excess by 1 stoichiometry relative to the stoichiometry corresponding to the chemical formula. 5-3.0wt%; (2) The polycrystalline material block is placed into an iridium crucible and placed in a melt heating zone, an interface control zone, a gradient transition zone and a slow cooling zone arranged sequentially along the pulling direction; the interface control zone, the gradient transition zone and the slow cooling zone are respectively equipped with independent heating elements and temperature sensors; the polycrystalline material block is heated to 1730-1800℃ to form a melt; (3) A calcium magnesium zirconium doped gadolinium gallium garnet seed crystal with a growth direction of <111> is used to sequentially perform crystal introduction, necking, shoulder formation, equal diameter growth and tailing; during the crystal growth process, Collect the temperature, crystal diameter and melt meniscus height of each temperature zone, and adjust the heating power of the interface control zone, gradient transition zone and slow cooling zone through a multivariable controller to keep the axial temperature gradient at the solid-liquid interface at 3.5-7.0℃ / cm, the axial temperature gradient of the part of the crystal located in the slow cooling zone at 0.5-2.5℃ / cm, and the maximum radial temperature difference between the center and the outer periphery on the same axial section of the crystal is not greater than 2.0℃; (4) After the end, let the crystal pass through the gradient transition zone and slow cooling zone in sequence. The cooling process is carried out in stages, and the maximum radial temperature difference is kept below 2.0℃ during the cooling process until the crystal temperature drops below 500℃. An integral, continuous zirconia-alumina composite radiation tube that runs through the three temperature zones is provided on the inner side of the interface control zone, gradient transition zone, and slow cooling zone. The effective heating sections of the heating elements in two adjacent temperature zones overlap each other by 5-20mm in the axial direction. The axial heights of the interface control zone, gradient transition zone, and slow cooling zone are 40-80mm, 60-120mm, and 80-160mm, respectively.

2. The method for controlling the growth of calcium-magnesium-zirconium-doped gadolinium-gallium garnet crystals in multiple temperature zones according to claim 1, characterized in that: In the chemical formula, 0.31≤x≤0.36, 0.25≤y≤0.32, 0.59≤x+y≤0.65, and the molar ratio of Ca to Mg is 0.95-1.15; the room temperature lattice constant of the prepared crystal is 12.450-12.510 Å.

3. The method for controlling the growth of calcium-magnesium-zirconium-doped gadolinium-gallium garnet crystals in multiple temperature zones according to claim 1, characterized in that: In step (1), Gd2O3 and Ga2O3 are dissolved in nitric acid solution, and calcium nitrate, magnesium nitrate and zirconium oxynitrate are added to form a mixed salt solution with a total metal ion concentration of 0.2-1.0 mol / L; Citric acid is added as a complexing agent, with a molar ratio of citric acid to total metal ions of 1.0-2.

0. The pH of the solution is adjusted to 6.5-8.0, a gel is formed at 80-120℃, and then calcined at 800-1050℃ for 2-6 hours.

4. The method for controlling the growth of calcium-magnesium-zirconium-doped gadolinium-gallium garnet crystals in multiple temperature zones according to claim 1, characterized in that: The median particle size of the primary particles in the nanocomposite precursor is 50-150 nm, and the particle size D90 is not greater than 300 nm. The particle size of the primary particles is obtained by statistical analysis of no less than 200 particles using transmission electron microscopy. The sum of the mass fractions of the garnet phase and the Ga2O3 compensating phase, as determined by Rietveld X-ray diffraction after sintering of the polycrystalline block, is not less than 99.0%, and the mass fraction of the Gd2Zr2O7 phase is not greater than 0.5%. In any five 100 μm × 100 μm scanning electron microscope energy spectrum scanning regions, the relative standard deviations of the atomic fractions of Ca, Mg, and Zr are not greater than 5%.

5. The method for controlling the growth of calcium-magnesium-zirconium-doped gadolinium-gallium garnet crystals in multiple temperature zones according to claim 1, characterized in that: The polycrystalline material is a columnar or sheet-like material with a diameter of 10-30 mm and a relative density of 55%-75%; an annular iridium cap is provided above the iridium crucible, and the central opening area of ​​the annular iridium cap is 20%-40% of the area of ​​the iridium crucible opening; the molten material and crystal growth are carried out in nitrogen or argon gas with a purity of not less than 99.999%, and the absolute pressure inside the furnace is 0.10-0.15 MPa.

6. The method for controlling the growth of calcium-magnesium-zirconium-doped gadolinium-gallium garnet crystals in multiple temperature zones according to claim 1, characterized in that: The axial temperature gradients at the solid-liquid interface during the necking stage, shoulder formation stage, constant diameter growth stage, and tailing stage are controlled to be 5.0-7.0℃ / cm, 4.0-6.0℃ / cm, 3.5-5.0℃ / cm, and 3.0-4.5℃ / cm, respectively. The axial temperature gradient is the slope of the linear fitting of the temperature-axial position curve within a 10mm axial interval centered on the solid-liquid interface. The height of the melt meniscus during the constant diameter growth stage is maintained at 0.8-2.5mm.

7. The method for controlling the growth of calcium-magnesium-zirconium-doped gadolinium-gallium garnet crystals in multiple temperature zones according to claim 1, characterized in that: The room temperature lattice mismatch rate between the seed crystal and the target crystal is no greater than 0.02%; the pulling speed during the constant diameter growth stage is 0.8-1.5 mm / h, the seed crystal rotation speed is 4-8 rpm, the target crystal diameter is 50-80 mm, and the deviation of the crystal diameter from the target diameter is kept within ±0.5 mm.

8. The method for controlling the growth of calcium-magnesium-zirconium-doped gadolinium-gallium garnet crystals in multiple temperature zones according to claim 1, characterized in that: After the end of the process, keep the crystal rotating at 1-3 rpm and perform segmented cooling according to the following cooling procedure: when cooling from the crystal growth termination temperature to 1400℃, the cooling rate is 5-15℃ / h; when cooling from 1400℃ to 900℃, the cooling rate is 10-25℃ / h; when cooling from 900℃ to 500℃, the cooling rate is 20-40℃ / h; after the temperature drops below 500℃, cool the furnace to room temperature.

9. The method for controlling the growth of calcium-magnesium-zirconium-doped gadolinium-gallium garnet crystals in multiple temperature zones according to claim 1, characterized in that: The diameter of the constant-diameter segment of the obtained crystal is not less than 50 mm and the effective length is not less than 80 mm; the lattice constant difference at different axial positions of the constant-diameter segment is not greater than 0.002 Å; the full width at half maximum (FWHM) of the X-ray rocking curve of the (888) crystal plane is not greater than 2.0′; and the dislocation density of the (111) crystal plane measured by phosphoric acid etching is not greater than 100 cm⁻¹. -2 The transmittance of a double-sided polished wafer with a thickness of 2mm is not less than 80% in the 380-3000nm wavelength band.

Citation Information

Patent Citations

  • Gadolinium illinium scandium gallium garnet crystal GYSGG and its smelt method crystal growth method

    CN101307496B

  • Method for growing sapphire crystal by wide seed crystal edge-defined film-fed growth method

    CN121951680A

  • Device and method for growing 6-inch ultra-low dislocation germanium single crystal through VGF + VB method

    CN122257098A